THE EFFECT OF USING ENGLISH CORNER TO IMPROVE THE STUDENTS’ SPEAKING SKILL AT 2nd SEMESTER OF STKIP QOMARUDDIN 2016 - Lailatul Masruroh (Edulitics (Education, Literature, and Linguistics) Journal, 2016)
Abstract: Speaking is one of the skills that is badly needed for everyoneincluding those who are studying English. It is due to the fact that they spendmuch of their time in school speaking. In speaking, people communicate theirideas, taught, and feeling to others. Therefore, speaking belongs to productiveskill which has complexity in practicing directly. This study was conducted toanswer the research problem that is “Is the result posttest scores by usingEnglish Corner of the students of 2nd semester of STKIP Qomaruddin higherthan the result of their pretest score in speaking achievement? Thus, it isintended to obtain reliable information whether there was a significantdifference between the result posttest and pretest score in the students’speaking achievement .The design of the study was pre experimental design. The samples of thestudy were taken from the students of second semester of STKIPQOMARUDDIN . The experimental group was taught speaking skill by usingEnglish corner technique. Before giving the treatment the students were givenpretest and After giving the treatment, the students were also given a post testfor collecting the data.The data of the test which were in the form of the gained score wasanalyzed by using t-test with the significant level of p=5%. It was found that themean score of the pretest was 38.50But the mean of posttest was 71.93 . Then, the statistical computation onthe gained score revealed that the t value was 21.296 while the t table value at p= 5% is 2.052. It shows that the obtained t value was much higher than that ofthe critical one. Thus, it is clear that the difference of the two means gainedscore was significant. Therefore, it can be concluded that the application ofEnglish Corner on students’ speaking achievement was most effective.Then, based on the result of this research, it is suggested to the Englishteachers to apply this method in the speaking class. Meanwhile, the researcherhopes that other researchers can use the findings as the basis to conduct otherresearch design. Keywords: Effectiveness, Improving, Speaking achievement, English Corner